Sufisme dalam Perspektif K.H. Muhammad Idris Jauhari - Amalih, Ihwan (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article explores Sufism in the perspective of K.H. Idris Muhammad Jauhari. It will also reveal the patterns of his mystical thought. In this study, the author finds that: firstly, in the view of Kiai Jauhari, Sufism is an attempt to straighten out the intention of heart and to understand the essence of deeds conducted by human beings in order to live a life to reach its final destination in accordance with the will of the Creator. Secondly, the patterns of Kiai Jauhari?s mystical thought are: a). Sufism developed by Kiai Jauhari built on a tradition of tasawuf akhlâqî (consistency to maintain Islamic orthodoxy, humanist Sufism, activist and functional, dichotomous relationship pattern between the servant and the Lord as well as the urgency of dhikr Allâh in the spiritual journey toward the Lord), b). Sufism developed and offered by Kiai Jauhari is an effort to redefine and reorient so that Sufism in both theoretical and practical aspect is no longer positioned as being elitist, mystical, and individualist. Kiai Jauhari has developed inclusive Sufism, which is easily accessible by all people. Thirdly, according to Kiai Jauhari there are six steps to become a Sufi, are: îqân al-nafs (convincing one?s self), taqwîn al-niyyah (straightening intention), al-dirâsah wa al-istitlâ? (learning and studying), al-tafakkur wa al-tadabbur (thinking and contemplation), al-takhallî wa al-tahallî (emptying and filling), and al-tajallî (manifestation).